Transport of palladium in urban water environments and its simulation: a case study of Haikou, Hainan Province, China. Issue 1 (2nd January 2021) - Liu, Yuyan; Ding, Fangfang; Zhang, Lan; Wang, Lin; Liu, Haofeng; Wu, Dan; Ji, Caiye; Fu, Bo
ABSTRACT: Palladium (Pd) is widely used in the production of automotive catalytic converters that serve to reduce toxic emissions from motor vehicles. The aim of this study was to explore the transport of Pd in the urban water environment. The results showed that the amounts of transported Pd in the pollution chain followed the order of rainfall runoff > estuary > receiving water body > wet deposition, indicating that rainfall runoff was the main source of Pd input. The amount of transported Pd might not depend entirely on the short-term Pd inputs from rainfall runoff and wet deposition. In the estuary, the phenomenon that Pd transport was dominated by suspended matter appeared for the first time in the entire pollution chain. Acertain amount of the inputted Pd was absorbed and accumulated in the urban water environment so that the inputted Pd was not completely outputted.